2016
DOI: 10.1111/bju.13526
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and establishment of a ward‐based geriatric liaison service for older urological surgical patients: Proactive care of Older People undergoing Surgery (POPS)‐Urology

Abstract: This is the first known paper describing the benefits of daily proactive geriatric intervention in elective and emergency urological surgery. The results suggest that using a multidisciplinary team board round helps to facilitate collaborative working between surgical and geriatric medicine teams. The GSCL enables systematic identification of patients who require a focused comprehensive geriatric assessment. There is potential to transfer the GSCL package to other surgical specialties and hospitals to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 13 publications
(14 reference statements)
2
46
0
Order By: Relevance
“…Understanding the contribution and interaction of both frailty and comorbidity may aid in surgical decision making, optimizing patients preoperatively, and tailoring interventions to the needs of patients with comorbidities, who are frail, or both. For example, perioperative interventions for patients with comorbidities may focus on polypharmacy, balancing potentially incompatible treatments for multiple diseases and prioritizing treatments, whereas frailty‐focused interventions may incorporate prehabilitation therapy, nutrition services, and involvement of geriatric providers throughout the perioperative period . Targeted interventions require accurate preoperative identification of the frail phenotype, which should be a routine part of preoperative assessment and is feasible in a busy surgical practice .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the contribution and interaction of both frailty and comorbidity may aid in surgical decision making, optimizing patients preoperatively, and tailoring interventions to the needs of patients with comorbidities, who are frail, or both. For example, perioperative interventions for patients with comorbidities may focus on polypharmacy, balancing potentially incompatible treatments for multiple diseases and prioritizing treatments, whereas frailty‐focused interventions may incorporate prehabilitation therapy, nutrition services, and involvement of geriatric providers throughout the perioperative period . Targeted interventions require accurate preoperative identification of the frail phenotype, which should be a routine part of preoperative assessment and is feasible in a busy surgical practice .…”
Section: Discussionmentioning
confidence: 99%
“…For example, perioperative interventions for patients with comorbidities may focus on polypharmacy, balancing potentially incompatible treatments for multiple diseases and prioritizing treatments, whereas frailty-focused interventions may incorporate prehabilitation therapy, nutrition services, and involvement of geriatric providers throughout the perioperative period. 22,40,41 Targeted interventions require accurate preoperative identification of the frail phenotype, which should be a routine part of preoperative assessment and is feasible in a busy surgical practice. 19 For example, Makary et al integrated a standardized frailty assessment into routine preoperative assessment, which consisted of a combination of self-report questions of recent weight loss; feelings of exhaustion; and physical activity as well as physical assessments, including grip strength and gait speed.…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary study by Braude et al [5] also demonstrated a reduction in complication rate and length of stay in urological patients >65 yrs. of age by the introduction of a geriatric liaison service.…”
Section: Discussionmentioning
confidence: 87%
“…This is now established practice. However it is only recently that this has been considered in other areas of surgical practice, specifically within urology [5]. The aim of this service evaluation was to assess the impact of age on the length of stay for patients admitted as an emergency with visible haematuria in our trust.…”
mentioning
confidence: 99%
“…Evidence from other sources has previously indicated that similar models of care can reduce complications and LOS in orthopaedic, urological and vascular surgical cohorts. 15,20,21 However, limited evidence has previously been published to demonstrate that the model of care can be successfully transferred to gastrointestinal surgery. Importantly, these data may indicate the potential value of this model of care to emergency general surgical services.…”
Section: Reductions In Losmentioning
confidence: 99%